Caridina sinanensis, a new species of stygobiotic atyid shrimp (Decapoda, Caridea, Atyidae) from a karst cave in the Guizhou Province, southwestern China - Xu, Da-Jian (Zookeys, 2020)
From a biodiversity survey of a subterranean habitat near Sinan County, Guizhou Province, southwestern China, a new atyid shrimp of the genus Caridina H. Milne Edwards, 1837, C. sinanensissp. nov. was discovered. The new species can be separated from other congeners based on a combination of characters including depigmentation in body and reduction of eyes, small pigment spot at the centre of the cornea, the shape of rostrum and the endopod of the 1(st) male pleopod, and the relatively longer appendix interna on the appendix masculina of the 2(nd) pleopod. Mitochondrial COI and 16S rRNA gene sequences also support the establishment of the new species. Information on the habitat, and the levels of threat are discussed to guide the conservation of C. sinanensissp. nov.